2022
DOI: 10.3390/ijerph19074110
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the COVID-19 Pandemic on the Assessment of Sexual Life—Repeated Cross-Sectional Surveys among Polish Adults in 2017, 2020 and 2021

Abstract: The study aims to investigate whether assessment of sexual life remained stable during the COVID-19 pandemic. Two surveys were conducted among Polish adults aged 18–70 years in June 2020 (n = 2042; perspective of last 2–3 months) and in June 2021 (n = 2418; last 12 months). Data from 2017 (n = 1980) were used as a reference point. Four questions allowed for defining five sexual life assessment profiles (k-means cluster analysis). Their characteristics were presented using 12 variables and 16 factors that contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…Similarly, the study by Tan et al [40] indicated that stress, fatigue, and low marital satisfaction levels were significant predictors of low sexual activity among Singaporeans. Among Polish participants, a lower frequency of sexual intercourse was related to pandemic-induced fatigue and stress and the permanent presence of others at home [44]. Finally, another study reported an increased risk of sexual dysfunction and depression among Polish adults during the pandemic [32].…”
Section: Discussionmentioning
confidence: 91%
See 3 more Smart Citations
“…Similarly, the study by Tan et al [40] indicated that stress, fatigue, and low marital satisfaction levels were significant predictors of low sexual activity among Singaporeans. Among Polish participants, a lower frequency of sexual intercourse was related to pandemic-induced fatigue and stress and the permanent presence of others at home [44]. Finally, another study reported an increased risk of sexual dysfunction and depression among Polish adults during the pandemic [32].…”
Section: Discussionmentioning
confidence: 91%
“…It is also important to note that some other studies reported positive changes in sexual behavior [38][39][40][41][42][43] and higher assessment of sexual satisfaction [42,44] during the COVID-19 pandemic. Arafat et al [38] found that 45% of the respondents from three Asian countries (Bangladesh, India and Nepal) reported that the lockdown impacted their sexual life.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Acute stress, which manifests itself throughout the period of social isolation, may affect patients’ sexual performance issues. It has been established that stress from social isolation is the fundamental cause of sexual dysfunction [ 30 ].…”
Section: Discussionmentioning
confidence: 99%